Robotic Management of Complex Obstructive Megaureter Needing Ureteral Dismembering and/or Tapering in Children: A Single-Center Case Series - Ciro Esposito; Lorenzo Masieri; Francesca Carraturo; Annalisa Chiodi; Claudia Di Mento; Giorgia Esposito; Mauro Porcaro; Daniella Araiza Kelly; Maria Escolino (Medicina)
Background and Objectives: Robot-assisted extravesical ureteral reimplantation (REVUR) has been described as valuable alternative to open reimplantation in the pediatric population. This study aimed to report the outcome of REVUR in children with complex obstructed megaureter (COM) needing ureteral dismembering and/or tapering. Materials and Methods: The records of patients with COM, who received REVUR with ureteral dismembering and/or tapering over the last 3 years (2021–2024), were retrospectively reviewed. The inclusion criteria for COM included previous surgery, paraureteral diverticula, or ectopic megaureter. Results: A total of 16 patients (15 boys), with a median age of 7.8 years (range 2–16), were treated over the study period. COM was associated with paraureteral diverticula (n = 6), previous failed endoscopic balloon dilation (n = 4), ectopic megaureter (n = 2), and previous bulking agent endoscopic injection causing iatrogenic ureteral obstruction (n = 4). Presentation symptoms included febrile urinary tract infections (n = 8), flank pain (n = 4), hematuria (n = 2), and pseudo-incontinence (n = 2). All surgical procedures were accomplished robotically without conversions or intra-operative complications. Ureteral tapering was performed in 7/16 (43.7%). The median operative time (including robot docking) was 220 min (range 155–290). The median length of stay was 3.8 days (range 3–7). The indwelling double J stent was removed 4–6 weeks postoperatively. Clavien 2 grade complications occurred postoperatively in 2/16 (12.5%). At median follow-up of 34.5 months, all patients were asymptomatic and showed improved hydroureteronephrosis on ultrasound and improved drainage on diuretic renogram. Conclusions: This study demonstrates that robot-assisted extravesical ureteral reimplantation is a safe and effective treatment for primary obstructive megaureter and other complex ureteral anomalies in our patient cohort. The procedure showed low complication rates, high success rates, and favorable long-term outcomes, supporting the feasibility and effectiveness of robotic surgery for these conditions.